2019
DOI: 10.1038/s41598-019-55299-0
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to guideline recommendations for coronary angiography in a poor South-East Asian setting: Impact on short- and medium-term clinical outcomes

Abstract: In South-East Asian populations and particularly in Indonesia, access to coronary angiography (CAG) is limited. We aimed to assess the adherence for undergoing CAG for indicated patients, according to the guideline recommendations. We then examined whether this adherence would have an impact on patients’ short- and medium-term mortality and morbidity. We consecutively enrolled 474 patients with acute and stable coronary artery disease who had indication for CAG at Makassar Cardiac Center, Indonesia from Februa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
(28 reference statements)
0
6
1
Order By: Relevance
“…When the CAG's benefits far outweigh its known risks, an appointment is scheduled after gaining consent from patients or their families 5 . The percentage of patients going through with their scheduled CAG reported in previous studies is rather low (57.6-59%) 6,7 . In other words, the reported incidence of the refusal of scheduled CAG on the part of patients is nearly half of the total scheduled cases 6,7 .…”
Section: Introductionmentioning
confidence: 73%
“…When the CAG's benefits far outweigh its known risks, an appointment is scheduled after gaining consent from patients or their families 5 . The percentage of patients going through with their scheduled CAG reported in previous studies is rather low (57.6-59%) 6,7 . In other words, the reported incidence of the refusal of scheduled CAG on the part of patients is nearly half of the total scheduled cases 6,7 .…”
Section: Introductionmentioning
confidence: 73%
“…Our previous study showed that a total of 62.3% (out of 477) CAD patients were smokers. [ 14 ] In this current study, all subjects were active smokers for at least 10 years with regular smoking of ≥ 10 cigarettes per day. Although several prevention attempts have been regulated, cigarette smoking is still the number 1 cause of preventable death in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to educational and financial level, the opinions of family and relatives, religious beliefs, social values, local culture, and fear of the hospital and medical interventions have always been influential factors, meaning that patients often end up with reluctant or rejection to recommended treatment. In our previous study, participants with lower educational attainment and lower-income was the majority of ACS patients who chose not to undergo CAG and subsequent intervention [ 48 ]. Inversely, a cross-sectional study by Peiris et al in 2020, showed that higher educational level and being on employment associated with a lower risk of CVDs in most LMICs [ 49 ].…”
Section: Cardiovascular Care and Practices In Lmicsmentioning
confidence: 99%